PENGEMBANGAN SISTEM INFORMASI BIMBINGAN DAN KONSELING DI SMK NEGERI 2 MAKASSAR - Ashabul Kahfi Rajab; Dr. Syamsurijal, M.T; Dr. Satria Gunawan Zain, M.T (UNM Journal of Technology and Vocational, 2023)
Guidance and Counseling (BK) as part of the school plays an important role in dealing with problems or violations committed by students so that an effective data storage is needed. Problems discoveredrelated to BK data processing at SMKN 2 (public vocational high school) Makassar is a process thatis still done manually, so it can potentially lose data due to scattered and also difficulties in findingstudent’s case data. The existence of a web-based guidance and counseling information system canassist teachers in processing and storing student’s case data, as well as easy access for parties whoneed student’s case data and information, such as the students’ parents. The development of this systemuses the prototype model with 4 main stages, namely: (1) needs analysis, (2) prototype design andmanufacture, (3) prototype evaluation, and (4) final product. The expert validation test was conductedby 2 lecturers to examine the validity of the software/program aspect and obtained an average of 4.9which met the valid criteria. The next test was on the practical and effective aspects which wasconducted by involving 30 respondents and the average practical aspect was 96% and the averageeffective aspect was 95%; thus, it was categorized as very practical and effective.